In-stent restenosis. Acute and long-term outcomes after excimer laser coronary angioplasty - Bejarano,Jorge (1999)
OBJETIVE: With the increased use of intracoronary stents, in-stent restenosis has become a clinically significant drawback in invasive cardiology. We retrospectively assessed the short- and long-term outcomes after excimer laser coronary angioplasty of in-stent restenosis. METHODS: Twenty-five patients with 33 incidents of in-stent restenosis treated with excimer laser coronary angioplasty (ELCA) were analyzed. Sixty-six percent were males, mean age of 73±11 years, and 83% were functional class III-IV (NYHA). ELCA was performed using 23 concentric and 10 eccentric catheters with a diameter of 1.6-2.2 mm, followed by balloon angioplasty (PTCA) and ultrasound monitoring. The procedure was performed in the following vessels: left anterior descending artery, 10; left circumflex artery, 8; right coronary artery, 6; left main coronary artery, 2; and venous bypass graft, 7. RESULTS: The ELCA was successful in 71% of the cases, and PTCA was 100% successful. The diameter of the treated vessels was 3.44±0.5mm; the minimal luminal diameter (MLD) increased from 0.30mm pre-ECLA to 1.97mm post-ELCA, and to 2.94mm post-PTCA (p<0.001). The percent stenosis was reduced from 91.4±9.5% before ECLA to 42.3±14.9% after ELCA and to 14.6 ± 9.3% after PTCA (p<0.001). Seventeen (68%) patients were asymptomatic at 6 months and 15 (60%) at 1 year. New restenosis rates were 8/33 (24.2%) at 6 months and 9 /33 (27.3%) at 12 months. CONCLUSION: ELCA is safe and effective for the treatment of in-stent restenosis. In the present sample, a slight increase in new restenotic lesions between 6 and 12 months was found.